Cefpodoxime Proxetil for Treatment of Acute Bacterial Bronchitis in Children - Yu.V. Marushko; T.V. Gishchak; G.G. Shef (Zaslavsky O.Yu., 2014)
Administration of cefpodoxime proxetil in combination treatment of children with acute nonobstructive bacterial bronchitis is highly effective and is associated with high degree of compliance and low incidence of side effects.